2019
DOI: 10.1186/s13046-019-1508-1
|View full text |Cite
|
Sign up to set email alerts
|

Musashi2 contributes to the maintenance of CD44v6+ liver cancer stem cells via notch1 signaling pathway

Abstract: BackgroundLiver cancer stem cells (LCSCs) contribute to hepatocellular carcinoma (HCC) development, metastasis, and drug resistance. MSI2 and Notch1 signaling are involved in the maintenance of CSCs. However, it is unknown whether MSI2 and Notch1 are involved in the maintenance of CD44v6+ LCSCs. Therefore, we investigated the clinical significance and function of MSI2 and its relationship with Notch1 signaling in the maintenance of stemness properties in CD44v6+ LCSCs.MethodsThe expression of MSI2 and CD44v6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Starbase and Targetscan databases predicted that there were binding sites between SOX2-OT and miR-143-3p, and between miR-143-3p and MSI2 ( Figure 3F ). MSI2 may be a potential molecular target for the treatment of HCC ( 29 ). Therefore, we speculated that miR-143-3p/MSI2 might regulate the behavior alternation of HCC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starbase and Targetscan databases predicted that there were binding sites between SOX2-OT and miR-143-3p, and between miR-143-3p and MSI2 ( Figure 3F ). MSI2 may be a potential molecular target for the treatment of HCC ( 29 ). Therefore, we speculated that miR-143-3p/MSI2 might regulate the behavior alternation of HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of MSI2 reversed the changes of cell malignant behaviors mediated by si-SOX2-OT#2. A study shows that MSI2 is positively correlated with high CD44v6 expression, which can promote the malignant behaviors of HCC cells ( 29 ). Collectively, our results confirmed that SOX2-OT could promote MSI2 by binding to miR-143-3p competitively, and finally promote the malignant behaviors of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A common dysregulated pathway in the development of cancer is the Notch1 signaling pathway, which has been shown to play a critical role in regulating stemness, proliferation, metastasis and drug resistance of cancer ( 36 38 ). As shown in a previous study, the hypoxia-induced Notch/SOX2 axis was crucial for maintaining cancer stem-like cells in ovarian cancer ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway are relevant to the procession of hepatocellular carcinoma(30), breast carcinoma (31), and gastric carcinoma (32), in uencing the proliferation, differentiation, and migration of tumor cells. The Notch signaling pathway is signi cant to the development of diversi ed cancers and can regulate the growth, survival, apoptosis, invasion and migration of all kinds of tumor cells, such as pancreatic carcinoma and liver cancer cells (33)(34)(35)(36). In addition, research has identi ed the relationship between tRFs and the Notch signaling pathway and shown that tRF/miR-1280 can bind with the 3'-UTR of JAG2 mRNA to decrease the synthesis of JAG2 (a ligand of Notch signaling pathway), thereby inactivating the Notch signaling pathway and reducing the proliferation and metastasis of CRC (37).…”
Section: Discussionmentioning
confidence: 99%